Monofloral Triadica Cochinchinensis Honey Polyphenols Improve Alcohol-Induced Liver Disease by Regulating the Gut Microbiota of Mice - Luo, Liping; Zhang, Jinping; Liu, Mingyan; Qiu, Shengrong; Yi, Shengxiang; Yu, Wenjie; Liu, Tao; Huang, Xueyong; Ning, Fangjian (Frontiers in Immunology, 2021)
Honey produced from medicinal plants holds great promise for human health. Increasing evidence suggests that the gut microbiota plays an important role in liver pathology after alcohol intake. The aim of this study was to identify the polyphenol composition of triadica cochinchinensis honey (TCH), and to study the potential effect of honey polyphenols on the regulation of gut microbes in mice with alcohol-induced liver injury and the improvement of alcohol-induced liver disease. For these purposes, a total of 190 compounds were identified and 27 of them were quantified by ultraperformance liquid chromatography coupled with quadrupole/time-of-flight mass spectrometry (UPLC-Q/TOF-MS) and we successfully established a mouse model of alcohol-induced liver injury. The results show that TCH polyphenols can significantly restore the levels of ALT and AST, and TCH intervention can significantly improve the pathological changes of liver tissue in alcohol-exposed mice. Additionally, a significant decrease was observed in Firmicutes/Bacteroidetes after TCH treatment. Moreover, KEGG pathways of ATP-binding cassette (ABC) transporters, two-component system and biosynthesis of amino acids enriched the most differentially expressed genes after TCH intervention for 8 weeks. Our results may have important implications for the use of TCH as a functional food component with potential therapeutic utility against alcohol-induced liver disease.